2011
DOI: 10.1371/journal.pone.0019338
|View full text |Cite|
|
Sign up to set email alerts
|

Passive Immunization Reduces Behavioral and Neuropathological Deficits in an Alpha-Synuclein Transgenic Model of Lewy Body Disease

Abstract: Dementia with Lewy bodies (DLB) and Parkinson's Disease (PD) are common causes of motor and cognitive deficits and are associated with the abnormal accumulation of alpha-synuclein (α-syn). This study investigated whether passive immunization with a novel monoclonal α-syn antibody (9E4) against the C-terminus (CT) of α-syn was able to cross into the CNS and ameliorate the deficits associated with α-syn accumulation. In this study we demonstrate that 9E4 was effective at reducing behavioral deficits in the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
422
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 403 publications
(433 citation statements)
references
References 61 publications
8
422
1
2
Order By: Relevance
“…Briefly, cells were grown in glass bottom dishes (MatTek Corporation, Ashland, MA, USA) and then postfixed in 1% glutaraldehyde, treated with osmium tetraoxide, embedded in epon araldite, detached from the glass coverslips and sectioned with the ultramicrotome (Leica, Wetzlar, Germany). Grids were analyzed with a Zeiss (Jena, Germany) OM 10 electron microscope as previously described 40 in order to evaluate the approximate numbers of APs per cell. For morphometric analysis of APs from each section, electron micrographs were obtained at a final magnification of  12 000, and a total of 20 cells were analyzed for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were grown in glass bottom dishes (MatTek Corporation, Ashland, MA, USA) and then postfixed in 1% glutaraldehyde, treated with osmium tetraoxide, embedded in epon araldite, detached from the glass coverslips and sectioned with the ultramicrotome (Leica, Wetzlar, Germany). Grids were analyzed with a Zeiss (Jena, Germany) OM 10 electron microscope as previously described 40 in order to evaluate the approximate numbers of APs per cell. For morphometric analysis of APs from each section, electron micrographs were obtained at a final magnification of  12 000, and a total of 20 cells were analyzed for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Different groups have investigated which region of the α-syn protein is the best target for the development of disease-modifying monoclonal antibodies. We and others have observed that antibodies that recognize an epitope in the C-terminus of α-syn are more effective at ameliorating the pathology in transgenic mouse models of PD, as they clear intracellular aggregates, inhibit α-syn propagation, and prevent C-terminus cleavage of the protein, which may lead to increased aggregation [54,84,120,121]. However, other groups have reported that antibodies against the N-terminus are also effective at clearing α-syn aggregates, reducing their propagation, and diminishing motor dysfunctions [122,123].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…Antibody-bound aggregates traffic more readily to the lysosomes of microglia, allowing for more effective breakdown and decreased cell-cell transfer of α-synuclein in a transgenic mouse model [109]. Both active and passive immunization against α-synuclein in a transgenic mouse model of PD decreased α-synuclein accumulation and decreased neurodegeneration and functional decline [110,111]. The first vaccination-based treatment for PD is currently in phase I clinical trials.…”
Section: Extracellular Clearance Degradation and Prevention Of Uptamentioning
confidence: 99%